Leadership Effectiveness of Millennial Leaders in New-Gen Social Enterprises based on the Workers' Perception of Leadership Styles or Behaviors of the Millennial Leaders - Chua, Howard (Archīum Ateneo, 2021)
This study looks into the leadership styles or behaviors of millennial leaders in social enterprises and how their workers perceive the millennials’ leadership styles in relation to the workers’ concept of an ideal leader. The social entrepreneur (millennial leader) and two employees/workers from six social enterprises were interviewed to understand (a) the millennial leader’s views on her own leadership styles and behaviors and (b) the workers’ concept of an ideal leader and their perception of the millennial leader’s style. The research shows that the social enterprise workers’ concepts of an ideal leader have strong alignment with the actual leadership qualities of their millennial leaders. In some cases, there is a blurring of the dichotomy of the ideal and actual leader persona in the sense that they see the millennial leader as the ideal leader. This matching has resulted in the workers’ positive impression and perceived effectiveness of these leaders, which is the concept behind Implicit Leadership Theory. The findings also show that the workers’ perception of the social entrepreneur often matches the self-description of the millennial leader. This could lead to a strengthening of the cited leadership behaviors, which is consistent with the Authentic Leadership Theory.